2003
DOI: 10.1007/s00259-002-1010-3
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of [ N -methyl - 11 C]α-methylaminoisobutyric acid in untreated head and neck cancer studied by PET

Abstract: Amino acid transport system A is expressed strongly in neoplastic cells. [ N-methyl-(11)C]alpha-Methylaminoisobutyric acid ((11)C-MeAIB) is a recently developed tracer for PET studies on system A amino acid transport. (11)C-MeAIB is a metabolically stable amino acid analogue which is transported from plasma into the tissue by system A. This study evaluated the kinetics of (11)C-MeAIB uptake from plasma into tumour tissue and normal tissues in 13 patients with untreated head and neck cancer. (11)C-MeAIB uptake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 18 publications
2
23
0
Order By: Relevance
“…A study in cultured human erythroleukemic (K562) cells using radiolabeled [ 14 C]MeAIB also gave the same result [34]. Given all of data, it is thought that system A is the principal [ 11 C]MeAIB transport pathway in in vivo human PET studies [19,20], although no human PET study has been conducted in the presence of amino acid transport inhibitors. In our study using four different types of human carcinoma cells we have shown that system A contributes more than 70% to [ 14 C]MeAIB uptake.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…A study in cultured human erythroleukemic (K562) cells using radiolabeled [ 14 C]MeAIB also gave the same result [34]. Given all of data, it is thought that system A is the principal [ 11 C]MeAIB transport pathway in in vivo human PET studies [19,20], although no human PET study has been conducted in the presence of amino acid transport inhibitors. In our study using four different types of human carcinoma cells we have shown that system A contributes more than 70% to [ 14 C]MeAIB uptake.…”
Section: Discussionmentioning
confidence: 81%
“…Compared with [ 11 C]MET, [ 11 C]MeAIB is metabolically stable [17] and it has been studied both pre-clinically and clinically. For example, [ 11 C]MeAIB has been shown to be useful in the measurement of amino acid uptake into skeletal muscle and in the diagnosis of malignant lymphoma and head and neck cancers [18][19][20]. In our institute, [ 11 C]MeAIB PET has proven useful in the diagnosis of chest diseases, especially in the differential diagnosis between sarcoidosis and metastasis [21].…”
Section: C]met Has Been As Widely Used In Brain Tumor Imaging As O-(2mentioning
confidence: 99%
“…The high degree of regulation of system A transport by factors such as amino acid availability [51,[63][64][65]190] has been proposed as a major source of this observed variability. In a more recent study using [ 11 C]MeAIB in 13 patients with known head and neck cancer, increased uptake was observed in all known lesions [191]. However, the uptake of [ 11 C]MeAIB was somewhat variable (SUV 2.4 to 11.5) and did not correlate with tumor proliferation rate as measured by Ki-67 staining or tumor grade.…”
Section: αα-Dialkyl Amino Acidsmentioning
confidence: 90%
“…Development of such novel tests is the exciting prospect that can now be glimpsed. Possibilities include measurement of transporter activity in the fragments of MVM plasma membranes, which are shed into maternal blood during every pregnancy (52) or the use of positron emission tomography with suitable tracer substrates to image placental transporter activity in utero: a suitable substrate for System A ([N-methyl-11C]alpha-methylaminoisobutyric acid) is now available (53). These specific diagnostic tests are essential prerequisites for developing the currently nonexistent in utero therapies for fetal growth anomalies, which are the ultimate goal.…”
Section: Discussionmentioning
confidence: 99%